The Ladies on the Hill: The female monastic communities at the aristocratic monasteries of Klosterneuburg and St. George´s in Prague - Hamburger, Jeffrey F. (Fokus Kloster, 2024)
"The Ladies on the Hill" is dedicated to the Benedictine monastery of St. George in Prague and the women's community alongside the Augustinian canons in Klosterneuburg. The volume discusses the rich heritage of these women's monasteries from historical, art historical, and music historical perspectives. The beginnings of dynastic family formation in the European Middle Ages were often linked to the founding of women's monasteries. This alone reveals the great political, social, and religious significance of the monasteries for the self-image of families, but also for the intergenerational anchoring of power and influence in space. Nevertheless, many of the once influential women's communities have remained largely unstudied to this day. This is particularly true of the oldest monastery in Bohemia, the Benedictine monastery of St. George in Prague, which existed for over 1,000 years. But the Klosterneuburg women's community alongside the Augustinian canons was also unjustly forgotten after its dissolution in 1568